2015
DOI: 10.1002/cncr.29233
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of ERG, TFF3, and SPINK1 for molecular subtyping of prostate cancer

Abstract: BACKGROUND In view of the marked molecular heterogeneity of prostate cancer (PCa), clinical and pathologic parameters alone may be unreliable for predicting disease outcomes after surgical intervention. The development of biomarkers may be helpful to estimate tumor heterogeneity and stratify patients in terms of their risk of progression. Levels of v‐ets avian erythroblastosis virus E26 oncogene homolog (ERG), trefoil factor 3 (TFF3), and serine peptidase inhibitor, Kazal type 1 (SPINK1) are commonly elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 43 publications
(100 reference statements)
5
20
2
Order By: Relevance
“…Data published on the prognostic significance of ERG remains conflicting with some studies pointing toward worse outcome while others showing no association or even suggesting favorable prognosis. However, the preponderance of data seems to suggest that ERG has no prognostic value in localized disease, while being associated with a worse prognosis in cohorts not managed surgically (such as watchful waiting cohorts) [22,28,[41][42][43][44][45]. In a recent study, our group was the first to report a significant association between ERG expression and a higher-stage disease, but not with post-surgical PSA relapse in patients with localized cancer.…”
Section: Discussionmentioning
confidence: 79%
“…Data published on the prognostic significance of ERG remains conflicting with some studies pointing toward worse outcome while others showing no association or even suggesting favorable prognosis. However, the preponderance of data seems to suggest that ERG has no prognostic value in localized disease, while being associated with a worse prognosis in cohorts not managed surgically (such as watchful waiting cohorts) [22,28,[41][42][43][44][45]. In a recent study, our group was the first to report a significant association between ERG expression and a higher-stage disease, but not with post-surgical PSA relapse in patients with localized cancer.…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies showed that overexpression of TFF3 promoted cell migration and invasion [6, 7, 11]. We next determined whether CDH1 mediated the effect of TFF3 on cell invasion in SiHa cells.…”
Section: Resultsmentioning
confidence: 98%
“…TFF3, behaved as an oncogene, promotes proliferation and invasion, improves survival, and increases oncogenicity in cancer cells, such as mammary carcinoma, gastric cancer and prostate carcinoma [5, 11]. TFF3 promoted epithelial tumorigenesis by inducing aberrant proliferation and inhibiting apoptosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, a majority of these studies reported SPINK1 overexpression mainly in androgen-induced E26 transformation-specific (ETS) gene fusion-negative tumors (31,32 ). In a recent study an inverse correlation between SPINK1 and trefoil factor 3 (TFF3) positivity and ETS negativity was shown, and in this TFF3 ϩ subgroup SPINK1 staining was associated with adverse clinical outcome (34 ). The findings that SPINK1 expression is confined to androgenindependent tumors and is higher in the metastases of castration-resistant prostate cancers than in primary tumors (32 ) suggest that SPINK1 may be involved in the metastatic processes.…”
Section: Prostate Cancermentioning
confidence: 99%